Lorentz‐Boost‐Driven Magneto‐Optics in a Dirac Nodal‐Line Semimetal - Wyzula, Jan; Lu, Xin; Santos‐Cottin, David; Mukherjee, Dibya Kanti; Mohelský, Ivan; Le Mardelé, Florian; Novák, Jiří; Novak, Mario; Sankar, Raman; Krupko, Yuriy; Piot, Benjamin A.; Lee, Wei‐Li; et al. (Advanced science, 2022)
Optical response of crystalline solids is to a large extent driven by excitations that promote electrons among individual bands. This allows one to apply optical and magneto‐optical methods to determine experimentally the energy band gap —a fundamental property crucial to our understanding of any solid—with a great precision. Here it is shown that such conventional methods, applied with great success to many materials in the past, do not work in topological Dirac semimetals with a dispersive nodal line. There, the optically deduced band gap depends on how the magnetic field is oriented with respect to the crystal axes. Such highly unusual behavior is explained in terms of band‐gap renormalization driven by Lorentz boosts which results from the Lorentz‐covariant form of the Dirac Hamiltonian relevant for the nodal line at low energies. Here the authors show that the magneto‐optical response of a topological Dirac semimetal with a dispersive nodal line can be understood in terms of pseudo‐relativistic Lorentz transformation. The observed variation of the optical band gap Δ is interpreted as Lorentz‐boost‐driven renormalization of energy, Δ → Δ/γ, where γ stands for the Lorentz factor defined by the mutual orientation of the applied magnetic field and nodal‐line direction.